2000
DOI: 10.1096/fasebj.14.9.1132
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adiposity by dietary calcium

Abstract: Recent data from this laboratory demonstrate that increasing adipocyte intracellular Ca(2+) results in a coordinated stimulation of lipogenesis and inhibition of lipolysis. We have also noted that increasing dietary calcium of obese patients for 1 year resulted in a 4.9 kg loss of body fat (P<0.01). Accordingly, we tested the possibility that calcitrophic hormones may act on adipocytes to increase Ca(2+) and lipid metabolism by measuring the effects of 1, 25-(OH)(2)-D in primary cultures of human adipocytes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
669
10
44

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 815 publications
(767 citation statements)
references
References 25 publications
44
669
10
44
Order By: Relevance
“…18,19 In addition, 1a, 25-(OH) 2 -D 3 also plays a role in regulating human adipocyte UCP2 expression, suggesting that the suppression of 1a, 25-(OH) 2 -D 3 and the resulting upregulation of UCP2 may contribute to increased rates of energy utilization. 10,11 Accordingly, the suppression of 1a, 25-(OH) 2 -D 3 by increasing dietary calcium attenuates adipocyte triglyceride accumulation and caused a net reduction in fat mass in both mice and humans in the absence of caloric restriction, 13 a marked augmentation of body weight and fat loss during energy restriction in both mice and humans, 13,20 and a reduction in the rate of weight and fat regain following energy restriction in mice. 14 Our previous data demonstrate that 1a, 25(OH) 2 D 3 stimulates Ca 2 þ signaling and suppresses UCP2 expression on human and murine adipocytes 11,14 and suppresses UCP3 expression in skeletal muscle in mice; 14 accordingly, dietary calcium suppression of ROS production is likely due to suppression of circulating 1a, 25(OH) 2 D 3 levels and resultant reductions in Ca 2 þ signaling and increases in UCP2 and UCP3 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 In addition, 1a, 25-(OH) 2 -D 3 also plays a role in regulating human adipocyte UCP2 expression, suggesting that the suppression of 1a, 25-(OH) 2 -D 3 and the resulting upregulation of UCP2 may contribute to increased rates of energy utilization. 10,11 Accordingly, the suppression of 1a, 25-(OH) 2 -D 3 by increasing dietary calcium attenuates adipocyte triglyceride accumulation and caused a net reduction in fat mass in both mice and humans in the absence of caloric restriction, 13 a marked augmentation of body weight and fat loss during energy restriction in both mice and humans, 13,20 and a reduction in the rate of weight and fat regain following energy restriction in mice. 14 Our previous data demonstrate that 1a, 25(OH) 2 D 3 stimulates Ca 2 þ signaling and suppresses UCP2 expression on human and murine adipocytes 11,14 and suppresses UCP3 expression in skeletal muscle in mice; 14 accordingly, dietary calcium suppression of ROS production is likely due to suppression of circulating 1a, 25(OH) 2 D 3 levels and resultant reductions in Ca 2 þ signaling and increases in UCP2 and UCP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Six mice randomly selected from each group were killed to provide baseline data and the remaining six mice in each group were put on a modified AIN 93 G diet 15 with sucrose as the sole carbohydrate source and providing 64% of energy, and fat increased to 25% of energy with lard as previously described. 13,14 Mice were studied for 9 days, during which food intake and spillage were measured daily and body weight, fasting blood glucose and food consumption assessed weekly. At the conclusion of the study, all mice were killed under isofluorane anesthesia and fat pads were immediately excised, weighed and used for further study, as described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat pad mass is lower after consumption of diets high in calcium carbonate or dairy calcium compared to an equicaloric, low-calcium, high-fat, high-sucrose diet. 10 Highcalcium diets result in greater loss of total and fat pad mass, increased lipolysis and lower lipogenesis compared to the control diet when the energy intake of obese mice is reduced to 70% of ad libitum consumption. 11 Unintentional weight loss (À4.9 kg of fat mass) occurred after 1 y of increased calcium intake (1000 mg/d) in obese African-Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological and experimental studies have shown that dietary calcium intake is negatively related to body mass index (BMI), both in adults [1][2][3][4] and in children. 5,6 Overall, each 300 mg increment in regular calcium intake is associated with approximately 1 kg less body fat in children, and 2.5-3.0 kg lower body weight in adults.…”
Section: Introductionmentioning
confidence: 99%